Does probiotic Kefir reduce dyslipidemia, hematological disorders and oxidative stress induced by zearalenone toxicity in wistar rats?. (June 2022) - Ben Taheur, Fadia; Mansour, Chalbia; Mechri, Sondes; Skhiri, Sihem Safta; Jaouadi, Bassem; Mzoughi, Ridha; Chaieb, Kamel; Zouari, Nacim
Abstract: Zearalenone (ZEA) is a toxic metabolite of the genus Fusarium, which causes hepatotoxicity and induces oxidative stress. Kefir is an important probiotic dairy-product showing important in vitro antioxidant potential. In this study, the effect of Kefir supplementation to mitigate ZEA toxicity in rats was investigated. Animals were divided into four groups of five rats each, which received sterile milk (200 μL/day) during the first week. Then, they were switched to Kefir (200 μL/day), ZEA (40 mg/kg b. w./day) and Kefir + ZEA for the second week. Hematological and biochemical parameters, as well as liver histological analysis were determined. Kefir administration prevented the changes occurred in the count of all blood cells, and improved the antioxidant enzymes in the liver, such as catalase, glutathione peroxidase and superoxide dismutase activities that increased by 6, 4.5 and 1.3 folds, respectively, compared to ZEA group. Interestingly, the concurrent regimen Kefir + ZEA removed ZEA residues in the serum and liver. Furthermore, the Kefir + ZEA group showed a reduction in the levels of bilirubin, alanine aminotransferase, aspartate aminotransferase, alkaline phosphatase and hepatic malonaldehyde by ∼82, 54, 66, 50 and 36%, respectively, compared to the ZEA group. The histopathological analysis showed a normal liver histological architecture in Kefir + ZEA group, while degenerative changes were observed in ZEA group. These results suggest that Kefir as probiotic consortium may have a hepatoprotective effect against ZEA poisoning. Graphical abstract: Image 1 Highlights: Zearalenone caused oxidative stress and liver damage in rats. Zearalenone induced disruption of hematological and biochemical parameters. Kefir improved the antioxidant defense systems in rats subjected to Zearalenone. Kefir prevented Zearalenone-induced hepatotoxicity in rats.